Estimativas de autovalores em subvariedades com curvatura media localmente limitada - Matos Neto, Manoel Vieira (2009)
We present a method to obtain lower bounds for first Dirichlet eigenvalue in terms of vector fields with positive divergence. Applying this to the gradient of a distance function we obtain estimates of eigenvalue of geodesic balls inside the cut locus and of domains in submanifolds with locally bounded mean curvature. For submanifolds of Hadamard manifolds with bounded mean curvature these lower bounds depend only on the dimension of the submanifold and the bound on its mean curvature.